ROLE OF CREDIT CARD IN THE DIGITAL PAYMENT SYSTEM: GROWTH ANALYSIS (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The present Government is aimed at transforming the country into a digital economy. It gives special attention for digital payments. In daily lives larger transactions are happening on payments and it has been resulted that enhance the better society, business and the economy at larger part. Over the past three years, digital payment system works with new payment modes along with existing payment system in order to increasing Person to Merchant (PtoM) as well as Person to Person (PtoP) payments. Among various modes of digital payments, credit card payment is one of the retail payment systems which have improved Person to Merchant payments. The usage of credit card depends on the users’ willingness to spend on credit basis. Thus, this study measure the growth of credit card payments with respect to volume and value of credit card payment transactions. These two parameters play a vital role in order to observe the users’ position in credit card payments. The 11 Financial Years from 2009-10 to 2019-20 were considered for the study. The analysis reveals that an average of 838.31 million transactions of credit card payment with the value of INR 2676.39 Billion has been takes place for the study period. Further, the growth prospect is expected that credit card payment takes place over INR 7000 Billion with over 2200 volume of transactions in 2022-23. Further, this study has been identified that most important credit card payment infrastructure namely number of outstanding credit cards, Point of Sales (POS) machines and volume of transaction on the growth on value of credit card payments for the reference period.